2015
DOI: 10.1111/jcmm.12666
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐138 inhibits cell proliferation and reverses epithelial‐mesenchymal transition in non‐small cell lung cancer cells by targeting GIT1 and SEMA4C

Abstract: Non‐small‐cell lung cancer (NSCLC) is one of the most common and lethal malignant tumours worldwide with a poor 5‐year survival rate. Recent studies indicated that miRNAs have been involved in the tumorigenic driver pathways in NSCLC, but the relevant molecular mechanisms are not well‐understood. In this study, we investigated the biological functions and molecular mechanisms of miR‐138 in human NSCLC. The effects of miR‐138 on the NSCLC cell growth and epithelial‐mesenchymal transition (EMT) were first examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 33 publications
(101 reference statements)
4
66
1
Order By: Relevance
“…Furthermore, miR-138 was found to be involved in the regulation of dendritic spine morphogenesis, in addition to the osteogenic differentiation of mesenchymal stem cells (21,22). Previously, deregulation of miR-138 was demonstrated to be associated with multiple types of human malignancies, generally acting as a tumor suppressor (23,24). For instance, miR-138 is able to suppress invasion and promote apoptosis in head and neck squamous cell carcinoma cells, via inhibition of the Rho GTPase signaling pathway (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-138 was found to be involved in the regulation of dendritic spine morphogenesis, in addition to the osteogenic differentiation of mesenchymal stem cells (21,22). Previously, deregulation of miR-138 was demonstrated to be associated with multiple types of human malignancies, generally acting as a tumor suppressor (23,24). For instance, miR-138 is able to suppress invasion and promote apoptosis in head and neck squamous cell carcinoma cells, via inhibition of the Rho GTPase signaling pathway (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Long et al demonstrated that inhibition of miR-138 in colorectal cancer cells resulted in a significant reduction of migration and invasion capacity by directly targeting TWIST2 (25). In non-small cell lung cancer, miR-138 decreased cell proliferation, migration in vitro and tumor growth in vivo, and increased cisplatin sensitivity through targeting multiple genes, including G protein-coupled receptor kinase interacting ArfGAP 1 (GIT1), semaphorin 4C, cyclin D3, Glucose regulated protein 124 (GRP124), enhancer of zeste homolog 2 and pyruvate dehydrogenase kinase 1 (26,(33)(34)(35). In oral squamous cell carcinoma, miR-138 inhibited cell proliferation via blockade of yes-associated protein 1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…These include two miRNAs, miR-210 and miR-138 (Ramachandran et al, 2012;Shang, Hong, Guo, Liu, & Xue, 2014). In relation to cancer biology miR-138 is identified as tumor-suppressive microRNA that inhibits cancer stem cell (CSC) phenotype, epithelial-to-mesenchymal transition (EMT), and metastasis in many cancer including lung, colorectal, and pancreas (Cristobal et al, 2015;Gao, Wang, Xie, Zhang, & Dong, 2015;Li et al, 2015;Xu et al, 2015).…”
Section: Expression and Regulationmentioning
confidence: 99%